2014
DOI: 10.1111/hel.12124
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Characteristics of Eradication Therapy of Helicobacter pylori in Japan: A Multi‐Generational Comparison

Abstract: Since CAM resistance and the incidence of side effects are higher in young individuals, it is especially important to select eradication regimens based on testing for antimicrobial susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 40 publications
4
50
0
Order By: Relevance
“…Moreover, the risk of gastric cancer rises with the progress of atrophy [30] [31] [32], and Kato et al [33] showed that gastric atrophy could develop in Japanese children of an average age of 12 years with H. pylori infection. In addition, we have shown significant over expression of several years old (57.9%) comparing to the elder group of more than 50 years old (35.1%) [40]. In this report, a high prevalence of CAM resistance (54.5%) was also observed, similar to past studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the risk of gastric cancer rises with the progress of atrophy [30] [31] [32], and Kato et al [33] showed that gastric atrophy could develop in Japanese children of an average age of 12 years with H. pylori infection. In addition, we have shown significant over expression of several years old (57.9%) comparing to the elder group of more than 50 years old (35.1%) [40]. In this report, a high prevalence of CAM resistance (54.5%) was also observed, similar to past studies.…”
Section: Discussionsupporting
confidence: 91%
“…Okamura et al had reported the existence of a region with a higher H. pylori resistance rate to MNZ in Japan. The population of infected patients had a MNZ resistance rate of 40.2% [40]. Although it is difficult to explain why this region has such a high incidence of MNZ resistant strains, it raises the possibility that increased MNZ resistance may be detected in the future, and cautious observation of susceptibility of H. pylori should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Okamura et al [41] reported that the proportion of CAM-resistant H. pylori was significantly higher in younger groups. They also reported that the proportion of CAMresistant H. pylori increased between 2000 and 2013, while the proportion of metronidazole-resistant H. pylori did 350 340 330 320 310 300 290 280 270 260 250 240 230 220 210 200 190 180 170 160 150 140 130 120 110 100 130 140 150 160 170 180 190 200 210 220 230 240 250 260 270 280 290 300 310 320 330 Cost ($) Cost-effectiveness analysis Figure 2: Cost-effectiveness graph.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional treatment of H. pylori infections includes the administration of antibiotics together with proton pump inhibitors [177], which often causes undesired side effects such as epigastric pain, nausea, and diarrhea [177]. Resistance of H. pylori to different antibiotic regimens including amoxicillin, clarithromycin, metronidazole, levofloxacin, tetracycline, and rifampicin has been reported in regional studies from different countries [178][179][180][181] and is particularly causing chronic health problems in children [182]. Consequently, APDT has been employed as a possible, more patient-friendly alternative to conventional therapy [183][184][185].…”
Section: Helicobacter Pylori (Gram-negative)mentioning
confidence: 99%